Perancangan Dan Pembuatan Sistem Informasi Perhotelan Pada Hotel Istana - Kurniawan Santoso; Silvia Rostianingsih; Alexander Setiawan (Jurnal Infra, 2015)
Hotel Istana is a hotel located in Jember, East Java. The current system is still not standarized. There are several business processes that have been computerized but some are still not computerized so there are still many shortcomings in record keeping. An example is the shortage of hotel revenue making bookkeeping errors can occur because of the missing memorandum that created the income statement is not accurate. For hospitality that made this system for the development of the old system.In this paper, the development process begins with analysis of the design with DFD, ERD, DocumentFlow. To determine the design of the field survey is needed first. Applications reservation system, check in, check out, a new report will be implemented at the Hotel Istana for the system in the hotel becomes more computerized and existing data can be stored in the database. This reduces the risk of data loss and also errors in the calculation. This thesis was made using Vb.net 2010 and Sql Server 2005 as the database.This application has been created with the features according to the system at Hotel Istana as check in, check out, reservation. Report feature has been able to assist owner monitoring development of business processes. Based on the questionnaire, this application has obtained 73.1% satisfaction rate.